Evidence for Ongoing Modeling-Based Bone Formation in Human Femoral Head Trabeculae via Forming Minimodeling Structures: A Study in Patients with Fractures and Arthritis - Sano, Hiroshige; Kondo, Naoki; Shimakura, Taketoshi; Fujisawa, Junichi; Kijima, Yasufumi; Kanai, Tomotake; Poole, Kenneth E. S.; Yamamoto, Noriaki; Takahashi, Hideaki E.; Endo, Naoto (Frontiers in Endocrinology, 2018)
Bone modeling is a biological process of bone formation that adapts bone size and shape to mechanical loads, especially during childhood and adolescence. Bone modeling in cortical bone can be easily detected using sequential radiographic images, while its assessment in trabecular bone is challenging. Here we performed histomorphometric analysis in 21 bone specimens from biopsies collected during hip arthroplasty, and we proposed the criteria for histologically identifying an active modeling-based bone formation, which we call a “forming minimodeling structure” (FMiS). Evidence of FMiSs was found in 9 of 20 specimens (45%). In histomorphometric analysis, bone volume was significant higher in specimens displaying FMiSs compared with the specimens without these structures (BV/TV, 31.7% ± 10.2 vs. 23.1 ± 3.9; p < 0.05). Osteoid parameters were raised in FMiS-containing bone specimens (OV/BV, 2.1 ± 1.6 vs. 0.6 ± 0.3%; p < 0.001, OS/BS, 23.6% ± 15.5 vs. 7.6 ± 4.2; p < 0.001, and O.Th, 7.4 μm ± 2.0 vs. 5.2 ± 1.0; p < 0.05). Our results showed that the modeling-based bone formation on trabecular bone surfaces occurs even during adulthood. As FMiSs can represent histological evidence of modeling-based bone formation, understanding of this physiology in relation to bone homeostasis is crucial.